Challenges in linking destinations’ online reputation with competitiveness - Patricia P. Iglesias-Sánchez; Marisol B. Correia; Carmen Jambrino-Maldonado (Tourism & Management Studies)
This study sought to examine how Web 2.0 conversations in social media platforms impact destinations’ reputation and how co-creation practices influence this process. The five most competitive destinations worldwide were included in the research. The results demonstrate that monitoring social media is a challenge in tourism but also a strategic tool to support decision-making processes and sustainable destination brand building. Various monitoring and analytic tools are currently available, but more models are needed to systematise and harness social media data for destination management organisations. The findings include tourists’ central role in destinations’ competitiveness through these visitors’ online posts about experiences and opinions, as well as key strategies for successful social media management based on this study’s results